Targeting the cancer microenvironment: inflammatory breast cancer management - Ueno, Naoto T. (Henry Stewart Talks, 2020)
Introduction to inflammatory breast cancer, Epidemiology of IBC, Approaches to treatment of IBC, Molecular analysis of IBC, The contribution of microenvironmental factors to the aggressiveness of IBC, Targeting the cancer microenvironmental factors for treating IBC, The involvement of macrophages and mast cells in the aggressiveness of IBC